2013
DOI: 10.1016/j.febslet.2013.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Influenza NS1 interacts with p53 and alters its binding to p53‐responsive genes, in a promoter‐dependent manner

Abstract: a b s t r a c tThe interplay between influenza A viruses (IAV) and p53 has only been reported in a limited number of studies, mainly focusing on the antiviral role of p53. We investigated the impact of IAV infection on p53 stability and transcriptional activity. Our results indicate that IAV-induced stabilization of p53 only partially correlates with modulation of p53 transcriptional activity measured during infection. Moreover, we show that the viral non-structural protein 1 (NS1) is able to inhibit p53 trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 22 publications
3
21
0
Order By: Relevance
“…NP impaired MDM2‐mediated p53 ubiquitination by associating with p53 to prevent interaction with MDM2 (Wang et al ., ). IVA non‐structural protein 1 (NS1) also enters the nucleolus (Melen et al ., 2007; 2012; Emmott et al ., ) and associates with p53 (Terrier et al ., ) but, in contrast to NP, inhibits p53‐mediated transcriptional activity and apoptosis (Wang et al ., ). Thus, it appears that IVA might mediate a complex‐regulatory interplay with the nucleolus/p53 to regulate apoptosis, possibly to inhibit antiviral apoptosis during early stages of infection, while inducing proapoptotic effects late in infection to facilitate viral spread.…”
Section: Viral Targeting Of the Nucleolusmentioning
confidence: 99%
See 1 more Smart Citation
“…NP impaired MDM2‐mediated p53 ubiquitination by associating with p53 to prevent interaction with MDM2 (Wang et al ., ). IVA non‐structural protein 1 (NS1) also enters the nucleolus (Melen et al ., 2007; 2012; Emmott et al ., ) and associates with p53 (Terrier et al ., ) but, in contrast to NP, inhibits p53‐mediated transcriptional activity and apoptosis (Wang et al ., ). Thus, it appears that IVA might mediate a complex‐regulatory interplay with the nucleolus/p53 to regulate apoptosis, possibly to inhibit antiviral apoptosis during early stages of infection, while inducing proapoptotic effects late in infection to facilitate viral spread.…”
Section: Viral Targeting Of the Nucleolusmentioning
confidence: 99%
“…NP impaired MDM2-mediated p53 ubiquitination by associating with p53 to prevent interaction with MDM2 . IVA non-structural protein 1 (NS1) also enters the nucleolus (Melen et al, 2007;Emmott et al, 2010a) and associates with p53 (Terrier et al, 2013) but, in contrast to NP, inhibits p53-mediated transcriptional activity and apoptosis (Wang et al, 2010b).…”
Section: Viral Control Of Nucleolar Function In Cellular Stress Respomentioning
confidence: 99%
“…Indeed, we recently reported that p53 isoforms are also differentially regulated in response to flu virus infection and play an active role in regulating flu virus production 84,9496…”
Section: Role Of P53 Isoforms In Human Cancer and Other Pathologiesmentioning
confidence: 99%
“…Therefore, IAV has developed different strategies to regulate host‐cell P53‐dependent pathways to ensure the viral life cycle. For instance, viral‐NS1 can inhibit P53 transcriptional activity and to mediate cell survival during infection . Importantly, the rescue of P53 activity during viral infection has become an area of a therapeutic option to limit viral replication and distribution .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, viral-NS1 can inhibit P53 transcriptional activity and to mediate cell survival during infection. 46 Importantly, the rescue of P53 activity during viral infection has become an area of a therapeutic option to limit viral replication and distribution. 47,48 While targeting Akt kinase and its connected signaling, mTOR and PI3K disturb IAV entry and inhibit viral replication.…”
Section: Discussionmentioning
confidence: 99%